1990
DOI: 10.1161/01.cir.82.1.60
|View full text |Cite
|
Sign up to set email alerts
|

Effect of atrioventricular interval during pacing or reciprocating tachycardia on atrial size, pressure, and refractory period. Contraction-excitation feedback in human atrium.

Abstract: To determine whether a contraction-excitation feedback mechanism exists in human atrium, we investigated the effects of varying the atrioventricular (AV) interval from 0 to 360 msec during AV pacing at a cycle length of 400 msec on atrial pressure, size, and refractoriness in 10 patients (group 1, without supraventricular tachycardia). The same parameters were determined in another 10 patients (group 2, with different spontaneous AV relations) during AV reciprocating tachycardia or AV nodal reciprocating tachy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
49
0
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(56 citation statements)
references
References 13 publications
6
49
0
1
Order By: Relevance
“…27 However, atrial pressure elevation caused by AV interval manipulation has been associated with either an increase or no change in atrial ERPs. 9,10 Our findings of nonuniform prolongation of atrial ERPs, increased PWD, and impairment of sinus node function after long-term loss of AV synchrony are consistent with those from prior human studies of short-term atrial dilatation and animal studies of long-term atrial dilatation. 5,9,18,20,21 Persistence of ERP adaptation to rate contrasts with animal studies of electrical remodeling that show loss of rate adaptation.…”
Section: Electrical Remodeling Associated With Atrial Dilatationsupporting
confidence: 87%
See 1 more Smart Citation
“…27 However, atrial pressure elevation caused by AV interval manipulation has been associated with either an increase or no change in atrial ERPs. 9,10 Our findings of nonuniform prolongation of atrial ERPs, increased PWD, and impairment of sinus node function after long-term loss of AV synchrony are consistent with those from prior human studies of short-term atrial dilatation and animal studies of long-term atrial dilatation. 5,9,18,20,21 Persistence of ERP adaptation to rate contrasts with animal studies of electrical remodeling that show loss of rate adaptation.…”
Section: Electrical Remodeling Associated With Atrial Dilatationsupporting
confidence: 87%
“…Human data have, thus far, been limited to short-term pacing studies; here, too, conflicting data exist. 9,10 An emerging body of evidence suggests that long-term asynchronous ventricular pacing (VVI) is associated with an increased incidence of AF; ongoing multicenter trials are addressing this issue. [11][12][13][14] The mechanism underlying this observation is unknown.…”
mentioning
confidence: 99%
“…This model mimics heart failure-related AF associated with regional atrial conduction slowing due to increased collagen turnover and interstitial fibrosis (16). However, it also results in substantial interanimal variability in AF production and in overt congestive heart failure, occasionally leading to premature death (prior to completion of the protocol) (11).An ideal AF model should be simple, clinically relevant (i.e., simulate human disease), and allow for reliable sustained AF production and thereby sensitivity to intervention (25).Based on these considerations and inspired by observations made in humans that a very short ventriculoatrial interval (during reciprocating tachycardia) can cause a marked increase in atrial pressure by inducing atrial contractions during mitral valve closure (18,20,31), we developed a fast simultaneous atrioventricular pacing (SAVP) model. This new model was designed to produce hemodynamic consequences that have been shown to lead to atrial electrical and structural remodeling and AF vulnerability (15).…”
mentioning
confidence: 99%
“…Based on these considerations and inspired by observations made in humans that a very short ventriculoatrial interval (during reciprocating tachycardia) can cause a marked increase in atrial pressure by inducing atrial contractions during mitral valve closure (18,20,31), we developed a fast simultaneous atrioventricular pacing (SAVP) model. This new model was designed to produce hemodynamic consequences that have been shown to lead to atrial electrical and structural remodeling and AF vulnerability (15).…”
mentioning
confidence: 99%
“…Unfortunately, the clinical data are less clear. Whereas Klein et al 44 reported a marked increase in atrial effective refractory period in association with increased atrial pressures mediated by a short AV interval, Calkins et al 45 found no meaningful change in a similar experiment. Thus, whereas AF certainly is more prevalent in patients with dilated left atria, atrial dilatation may be due to many factors, including anatomic remodeling and scarring due to chronic increases in pressures, ischemia, or neurohormonal alterations.…”
Section: Atrial Fibrillationmentioning
confidence: 94%